2019
DOI: 10.4028/www.scientific.net/kem.805.76
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Air Permeability of Cotton-Fibre-Based Socks

Abstract: Socks are the clothing preserving the foot in thermal neutrality and preventing foot from blister generating. The development of socks has been diversified like the type, materials, and function, etc. Socks with good quality are conducive to prevent foot disease or smelly odor from foot. The wearing comfort of socks can be affected by the fabric properties of air permeability. The present study aims to investigate the relationship between the fabric parameters and air permeability of knitted socks fabric. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Air permeability is an important comfort factor for transporting moisture or vapor from the skin. Air permeability is a function of the thickness and surface porosity of the knit [ 33 , 34 ] and ensures the breathability of the socks.…”
Section: Introductionmentioning
confidence: 99%
“…Air permeability is an important comfort factor for transporting moisture or vapor from the skin. Air permeability is a function of the thickness and surface porosity of the knit [ 33 , 34 ] and ensures the breathability of the socks.…”
Section: Introductionmentioning
confidence: 99%
“…found that the percentage of cotton fibers may negatively affect the air permeability of the fabric. 32 In knitted fabrics, air permeability can decrease with an increase in yarn count and thickness. 6 Nevertheless, Fabric B is the preferred fabric for sports-abaya from the air permeability point of view.…”
Section: Resultsmentioning
confidence: 99%
“…The highest increase was observed in the sock samples of series B (Table 8 and Figure 8a), which had a better ability to absorb moisture. The higher air flow ensures the breathability of the socks and was primarily influenced by the thickness of the fabric and the open porosity [19,48]. As shown in Table 8, permeability to air decreased in all socks with a more compact structure (series B and C), whereas untreated socks made of lyocell fibers were more breathable (Table 8 and Figure 8b).…”
Section: Comfort Quality Assessment Of the Socksmentioning
confidence: 91%
“…Many scientific studies have analyzed the performance of socks made of a high cotton content plated or blended with various synthetic fibers. They mostly refer to the comfort properties of the socks, e.g., comfort pressure [11][12][13], sock-skin friction [10,13], physiological and sensory parameters [13,14], thermal properties [15][16][17], moisture management, and air permeability [18][19][20], and/or to the usage properties of the socks, e.g., abrasion resistance, pilling performance [9,20,21], and dimensional stability [4,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%